The relationship between gluten proteins and baking quality - Móré, Mariann; Győri, Zoltán; Sipos, Péter (Acta Agraria Debreceniensis, 2012)
Wheat, one of the most important cereals, is grown on the largest area in Hungary. During hydration of storage proteins of wheat – gliadin and glutenin – the gluten complex is evolved. The gliadin is responsible for the extensibility of gluten complex as well as the glutenin for the strength of gluten. The structure, composition and rheological properties of gluten proteins influence significantly the baking quality. The gliadin/glutenin ratio and the quality and structure of glutenin fraction play the most important role in evolving gluten complex. Changes in the steps of breadmaking technology also have effect on the quality of product. Several tests proved that the higher glutenin content increases the strength of dough while the higher gliadin content increases the extensibility of dough and decreases maximum resistance to extension. The monomer gliadins play a great part in plasticity of glutenin polymer. The quality of glutenin fraction significantly influences the evolving gluten complex, because of the spiral structure of glutenin which deforms under stress conditions, then the β-spiral structure resumes their original conformation by releasing from stress.The final quality of product evolves as a result of complex characteristics of wheat proteins, so detailed knowledge on the roles of different protein compounds is the base of the quality oriented product development.